2015
DOI: 10.1007/s10856-015-5386-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun scaffolds of silk fibroin and poly(lactide-co-glycolide) for endothelial cell growth

Abstract: Electrospun scaffolds of silk fibroin (SF) and poly(lactide-co-glycolide) (PLGA) were prepared to mimic the morphology and chemistry of the extracellular matrix. The SF/PLGA scaffolds were treated with ethanol to improve their usability. After ethanol treatment the scaffolds exhibited a smooth surface and uniform fibers. SF transformed from random coil conformation to β-sheet structure after ethanol treatment, so that the SF/PLGA scaffolds showed low hydrophilicity and dissolving rate in water. The mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Various bioinert and bioactive molecules such as poly(ethylene glycol) (PEG), zwitterionic polymers, heparin, silk-fibroin and gelatin have been used to improve the hemocompatibility of scaffolds. [2][3][4][5][6][7][8][9][10][11] The modification can improve the hydrophilicity and reduce their interaction with proteins and platelets, thus significantly enhancing the hemocompatibility. [12][13][14][15] In order to prevent thrombosis and restenosis in implants, rapid endothelialization which can form a robust and confluent endothelial cell (EC) monolayer has been considered to be another promising method.…”
Section: Introductionmentioning
confidence: 99%
“…Various bioinert and bioactive molecules such as poly(ethylene glycol) (PEG), zwitterionic polymers, heparin, silk-fibroin and gelatin have been used to improve the hemocompatibility of scaffolds. [2][3][4][5][6][7][8][9][10][11] The modification can improve the hydrophilicity and reduce their interaction with proteins and platelets, thus significantly enhancing the hemocompatibility. [12][13][14][15] In order to prevent thrombosis and restenosis in implants, rapid endothelialization which can form a robust and confluent endothelial cell (EC) monolayer has been considered to be another promising method.…”
Section: Introductionmentioning
confidence: 99%
“…It's well known that the tensile strength of natural coronary artery is about 1.4-11.14 MPa, and elongation at break is usually above 40% [52]. Previous studies showed that the tensile strength and elongation at break of PLGA-based nanofibrous scaffolds were about 2-6 MPa and 80%-140% [5,[53][54][55][56]. Here, the tensile strength and elongation at break of PLGA and P(LA-co-GA-co-MMD) nanofibrous scaffolds at dry condition were in the range of 2.63-3.23 MPa and 84%-117%, respectively, which could meet the mechanical requirement for transplantation of vascular scaffolds.…”
Section: Mechanical Properties Of Plga and P(la-co-ga-co-mmd) Scaffoldsmentioning
confidence: 99%
“…However, the small-diameter, synthetic vascular grafts are encountered in several problems such as thrombosis, intimal hyperplasia, and lower long-term patency rates in clinical application [1,4]. The ideal vascular tissue engineering scaffolds should be designed to mimic the native extracellular matrix (ECM) in order to regulate cellular behavior [5]. Native ECM is an interconnected 3D porous structure consisting of proteins and carbohydrate biopolymers, which provides suitable environment for cells to adhere, grow, and proliferate [6].…”
Section: Introductionmentioning
confidence: 99%
“…Only few examples among many are currently presented. Some works report on electrospinning for hydrophilic and biodegradable planar devices of SF/PLGA or hybrid salt‐leached porous scaffolds on solid film support . An interesting improvement of the lyophilization‐based method was recently presented in a group of works .…”
Section: Formulated Products From Processed Rsfmentioning
confidence: 99%